TANTANGAN PENGEMBANGAN E-GOVERNMENT DI DESA PAGARUYUNG KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2024 - Mubarokah, Nur Lailatul; Nasution, Hazqon Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The development of information and communication technology has driven the transformation of traditional government towards a digital-based government system or e-government. Village governments are required to be able to follow this development in order to improve the quality of effective, efficient, transparent, and accountable public services. However, in reality, many villages still face challenges in the process of implementing e-government. Pagaruyung Village, Tapung District, Kampar Regency, is one example where the implementation of e-government has not been running optimally. The available village website only provides basic information, and has not been able to provide online public services. Based on these problems, this study aims to describe the readiness of Pagaruyung Village in developing e-government and identify the challenges faced in its implementation. This study uses a qualitative approach with a descriptive method. Data were collected through interviews and documentation studies. The study was analyzed using the theory of Indrajit (2007) with three main indicators: support, capacity, and value. The results of the study indicate that the readiness of Pagaruyung Village is still in the early stages. The village website has not been used as a means of online public services, and only provides general information. The main challenges faced include limited internet networks, minimal special budget for technology development, low human resource capacity in the field of information technology, and the absence of special regulations at the village level that regulate e-government management. Keywords: Challenges, E-Government, Village Government